Adding an International Student’s Voice to the Pandemic Discourse as Thinkers, not Subjects: Reflections on Power, Stillness and Humanness - Lipura, Sarah Jane (Journal of International Students, 2021)
As of this writing, the impact of the COVID-19 pandemic on international higher education is continuously being documented, drawing enough, if not too much, attention towards international students. However, the voices of international students remain muted such that much of what has been said about their experience do not directly come from them but from those who claim to speak on their behalf. In this essay, I attempt to add an international student voice to the pandemic discourse by shifting attention to international students not as subjects but as thinkers and co-producers of knowledge in their own right, in hope of also contributing to the broader conversation about ethics and responsibility surrounding international education and international student mobility research and practice. I do so by sharing my own reflections on the crisis and its critical relation to power, stillness and humanness.